Modeling and active vibration control of a coupling system of structure and actuators. (February 2016) - Liu, Jinxin; Zhang, Xingwu; Chen, Xuefeng
A model is extremely important to the controller designing and system analysis of an active vibration control system. However, the influence of actuators is always ignored by considering them as proportion links when modeling the control system. In this work, a joint model of a clamped-free shell structure and electrodynamic actuators was constructed. The shell was modeled using the finite element method while the actuators were simplified as lumped parameter models. It was found that the connections of actuators diminish the natural frequencies and smooth the resonance peaks of the structure. The optimal configuration of actuators and sensors was studied by harmonic response analysis and modal analysis. It was suggested to avoid the central line and give priority to the free end or the edges of the clamped-free shell when mounting actuators and sensors. The active control was carried out using the FXLMS algorithm, which effectively suppressed the disturbance of the vibration source. The control was conducted point by point on the transient response model of the structure and can easily be extended to a real life system.